A taphonomic study on the skeletal remains of Cervus (Sika) grayi from layer 3 of the Peking man site at Zhoukoudian during the 2009–2010 field seasons. (2nd May 2016) - Zhang, Shuangquan; Chen, Fuyou; Zhang, Yue; Li, Jingshu; Zhang, Xiaoling; Gao, Xing
Abstract: Re-excavation of the Peking man site at Zhoukoudian was initiated in 2009. A taphonomic analysis of the skeletal remains of Cervus ( Sika ) grayi, a dominant species from Layer 3 of the extant West Section of the site strongly negates a role played by hominins in the accumulation and modification of the bones. Instead, it is argued here that some individuals of this medium-sized deer species were probably trapped in the cave by accident and eventually preserved in situ in the Quaternary sediments. The virtual absence of stone artifacts and human skeletal remains from the 2009–2010 field seasons has further strengthened this conclusion. Bearing in mind evidence of a series of cave collapse episodes, we tentatively propose that the cave morphology during the formation of Layer 3 at the West Section was probably inhospitable to Homo erectus pekinensis .